COMPARATIVE FOURIER TRANSFORM INFRARED AND X-RAY POWDER DIFFRACTION ANALYSIS OF NATURALLY OCCURRED K-FELDSPARS - Theodosoglou, E.; Koroneos, A.; Soldatos, T.; Zorba, T.; Paraskevopoulos, K. M. (Bulletin of the Geological Society of Greece, 2010)
Natural K-feldspars from igneous rocks have been examined by means of X-ray powder diffraction (XRPD) and Fourier transform infrared (FTIR) spectroscopy in the spectral range 400-1400 cm-1, where the Si-Al-O bonds exhibit the dominant vibrations. From the XRPD analysis three species have been distinguished, i.e. microclines (3 samples), orthoclases (4 samples) and sanidines (3 samples); their unit cell parameters were calculated. The FTIR transmittance spectra of all samples have common bands at 426, 463, 584, 604, 726 and 772 cm-1 and some additional features. The spectra of sanidine and orthoclase exhibit fewer and broader bands than the microclines’, especially in the area 1000-1200 cm-1. The differences in their spectra are located in four bands. The bands at around 536-538 and 646-648 cm-1 in the spectrum of microcline, are shifted at around 542-544 and 640-642 cm-1 in the spectrum of orthoclase and at around 546 and 636 cm-1 in the spectrum of sanidine. Four bands at 1010, 1050, 1090 and 1136 cm-1 in the spectra of microcline are substituted with two quite broad bands at about 1030 and 1125 cm-1 in the spectra of orthoclase and sanidine. These differences are attributed to different degree of Al-Si ordering in the structure of K-feldspars.